2020
DOI: 10.1177/0969733020948112
|View full text |Cite
|
Sign up to set email alerts
|

Unmet care needs of older people: A scoping review

Abstract: The aim was to synthesize the findings of empirical research about the unmet nursing care needs of older people, mainly from their point of view, from all settings, focusing on (1) methodological approaches, (2) relevant concepts and terminology and (3) type, nature and ethical issues raised in the investigations. A scoping review after Arksey and O’Malley. Two electronic databases, MEDLINE/PubMed and CINAHL (from earliest to December 2019) were used. Systematic search protocol was developed using several term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 98 publications
3
64
0
Order By: Relevance
“…Care partners were also involved. e items generated were consistent with a scoping review carried out by Kalánková et al and a previous European cross-sectional survey [15,16].…”
Section: Action Plan For Implementing the Interventionsupporting
confidence: 54%
See 1 more Smart Citation
“…Care partners were also involved. e items generated were consistent with a scoping review carried out by Kalánková et al and a previous European cross-sectional survey [15,16].…”
Section: Action Plan For Implementing the Interventionsupporting
confidence: 54%
“…Care partners were also involved. The items generated were consistent with a scoping review carried out by Kalánková et al and a previous European cross-sectional survey [ 15 , 16 ]. This study was carried out as part of an audit of service provision and therefore no specific ethical approval was deemed to be required.…”
Section: Introductionmentioning
confidence: 61%
“… 40 Another review study found that the care needs of older adult patients, especially basic human needs, are often overlooked and neglected in care plans. 41 Neglecting physical needs related to the daily life activities of patients is a common event in many health centers, to the extent that it has become a global nursing issue. 41 , 42 In this regard, the WHO indicated that these omissions could directly or indirectly harm older adult patients and negatively affect healthy aging at home and in the community.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should include the diagnosis of cognitive functions and patients' ability to express their needs [49]. The expectations of institutionalized older patients remain underdiagnosed and untreated [50]. Future studies should also verify the relationship between global and disease-specific PA and determine which of them to use in successful interventions and how.…”
Section: Discussionmentioning
confidence: 99%